2005
DOI: 10.1002/app.21740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mixing process on electromagnetic interference shielding effectiveness of nickel/acrylonitrile–butadiene–styrene composites

Abstract: This article reports the effect of the mixing process on the electromagnetic interference (EMI) shielding effectiveness of nickel/acrylonitrile-butadiene-styrene (ABS) composites. Nickel in either powder or filament form was used as the filler material. It was mixed with ABS by two mixing processes: one was the Brabender-mixing method, in which nickel was mixed in the polymer melt by a strong shear at high temperatures, and the other was a simple dry mixing method performed in a centrifugal ball mill. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 7 publications
(6 reference statements)
1
27
0
Order By: Relevance
“…This is called as electromagnetic interference (EMI). EMI may cause malfunction to medical apparatus, industry robots or even cause harm to human body and become one of public nuisances [3][4][5][6]. Therefore, in order to alleviate these troubles the development of EMI shielding materials for microwave and millimeter waves are receiving increasing attention briskly.…”
Section: Introductionmentioning
confidence: 99%
“…This is called as electromagnetic interference (EMI). EMI may cause malfunction to medical apparatus, industry robots or even cause harm to human body and become one of public nuisances [3][4][5][6]. Therefore, in order to alleviate these troubles the development of EMI shielding materials for microwave and millimeter waves are receiving increasing attention briskly.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the characteristics and loading level of the conductive fillers, many other factors might also affect the conductive performance and EMI shielding effectiveness of polymer–matrix conductive composites. For example, Chou et al reported that when nickel powders were mixed in acrylonitrile‐butadiene‐styrene (ABS) melt using strong shearing at high temperatures (Brabender‐mixing method), the resulting composite sample with 15 vol % Ni powders had a very poor EMI shielding effectiveness of 4.8 dB, while the composite prepared using dry‐mixing method had a high EMI shielding effectiveness of about 54 dB (low nickel level of 5 vol %) 20. In the present study, the resin‐based conductive composites were prepared at room temperature using MMA homopolymer and cellulose acetate butyrate as the mixed resin and the same kind of nickel powders (International Nickel Company, type T255) as the conductive fillers, making use of simple solution‐blending technology.…”
Section: Resultsmentioning
confidence: 99%
“…Typical metals such as Ni, Ag, and Cu are the most commonly used metallic fillers for EMI shielding, and Ni, in particular, offers an appropriate choice owing to its lower cost than silver and better thermal stability than copper 17. Unfortunately, a limited amount of reports is currently available on Ni‐filled, and in particular, fine Ni‐filled conductive composites, which might be due to the difficulties in fabrication and dispersion as well of the fine Ni particles 18–20. To fabricate metal powders with desired properties via economical routes, the reduction of nickel salts in aqueous solution is usually tried for the preparation of fine nickel powders 21–23.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical conducting polymers and advanced composites have gained increasing attention as replacement for metals in EMI shielding applications [3]- [6]. In particular, carbon-based composites have been extensively investigated due to their superior mechanical properties and lightweight with respect to metals.…”
Section: Introductionmentioning
confidence: 99%